2019
DOI: 10.3390/cancers11101493
|View full text |Cite
|
Sign up to set email alerts
|

Antileukemic Efficacy in Vitro of Talazoparib and APE1 Inhibitor III Combined with Decitabine in Myeloid Malignancies

Abstract: Malignant hematopoietic cells of myelodysplastic syndromes (MDS)/chronic myelomonocytic leukemias (CMML) and acute myeloid leukemias (AML) may be vulnerable to inhibition of poly(ADP ribose) polymerase 1/2 (PARP1/2) and apurinic/apyrimidinic endonuclease 1 (APE1). PARP1/2 and APE1 are critical enzymes involved in single-strand break repair and base excision repair, respectively. Here, we investigated the cytotoxic efficacy of talazoparib and APE1 inhibitor III, inhibitors of PARP1/2 and APE1, in primary CD34+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…APEX1 inhibitor has demonstrated a promising toxicity on primary AML cells in vitro, alone or in association with hypomethylating agent decitabine or PARP (poly(ADP-Ribose) polymerase) inhibitor talazoparib. Even if APEX1 expression levels did not significantly differ between responding and non-responding AML cells, APEX1 inhibitor appeared promising in normal karyotype AML (83% of the APEX1 inhibitor "responders") [59]. Our data support the potential therapeutic interest of DNA damage signaling and DNA repair inhibitors in CN-AML.…”
Section: Discussionsupporting
confidence: 58%
“…APEX1 inhibitor has demonstrated a promising toxicity on primary AML cells in vitro, alone or in association with hypomethylating agent decitabine or PARP (poly(ADP-Ribose) polymerase) inhibitor talazoparib. Even if APEX1 expression levels did not significantly differ between responding and non-responding AML cells, APEX1 inhibitor appeared promising in normal karyotype AML (83% of the APEX1 inhibitor "responders") [59]. Our data support the potential therapeutic interest of DNA damage signaling and DNA repair inhibitors in CN-AML.…”
Section: Discussionsupporting
confidence: 58%
“…In preclinical studies, APEX1 inhibitor has demonstrated promising toxicity on primary AML cells in vitro, alone or in association with hypomethylating agent decitabine or with PARP inhibitor talazoparib. Even if APEX1 expression levels did not significantly differ between responding and non-responding AML cells, APEX1 inhibitor appeared promising in normal karyotype AML (83% of the patients with response to APEX1 inhibitor) [ 65 ]. Moreover, several other compounds targeting proteins involved in DNA repair mechanisms have already shown promising results as potential new anti-cancer drugs in pre-clinical studies, such as BLM [ 66 ], WRN [ 67 ], RAD52 [ 68 ], or MRE11 [ 69 ] inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism seems to be specific for leukemia stem cells and enables them to escape immune surveillance and later to cause relapse of disease (69). This opens the possibility to use PARP inhibitors for AML patient (70), an approach that the first clinical trials are currently assessing (71)(72)(73).…”
Section: Regulation Of Nkg2d Ligandsmentioning
confidence: 99%